Chat with our AI personalities
-8z + 5z = -3z
3z + 8 + 2z + 6 = 5z + 14
9z-5z = 30+z 3z = 30 z = 10
Mid-point: (3z+z)/2, (2z+8z)/2 = (2z, 5z) Slope: (8z-2z)/(3z-z) = 6z/2z = 3 Perpendicular slope: -1/3 Equation: y -5z = -1/3(x -2z) => y = -1/3x+2z/3+5z => y = -1/3x+17z/3 General form of the bisector equation: x+3y-17z = 0
We can simplify this expression by combining the like terms. Here the likes terms are the z's and the x's.2z + 3z + 5z = 10z. (If we have 2 of something and add three of the same thing and then 5 of the same thing we will end up with 10 of that thing).Likewise we can combine the x's.6x - 2x = 4x. (You could think of this as 6x + - 2x if this helps with the idea of "combining".)Therefore we are able to simplify this expression as:2z + 3z + 5z + 4 + 6x - 2x = 10z + 4 + 4x.